Modelling the radiation efficiency of orthotropic cross-laminated timber plates with simply-supported boundaries. (1st January 2019) - Santoni, Andrea; Schoenwald, Stefan; Fausti, Patrizio; Tröbs, Hans-Martin
Abstract: In this paper two prediction models to evaluate the radiation efficiency of orthotropic plates, developed with different approaches, are presented. A sound radiation model, based on an analytical/modal approach, is developed for a thin orthotropic plate, with the principal directions aligned with the edges. The model allows to consider the contribution of each mode, either resonant or non-resonant, as well as the influence of fluid loading on the plate dynamic response and on sound radiation. Moreover, a statistical model to evaluate the average radiation efficiency, based on a non-modal approach, which only considers the contribution of resonant modes, is presented. These two models have been used in order to predict the radiation efficiency of orthotropic cross-laminated timber (CLT) plates. CLT is an engineered wood material constituted by an odd number of lumber beams glued together, which have become very popular in the last twenty years in the building construction market. Due to their layered structure, CLT plates might exhibit a highly orthotropic behaviour. Both prediction models are validated by comparing the simulated results with the experimental radiation efficiency, obtained by means of vibro-acoustic measurements on three CLT plates. Finally, the influence of fluid loading on sound power radiated by CLT plates is investigated.